Pharmacokinetics and Tolerability of Oral Dosage Forms of Huperzine A in Healthy Chinese Male Volunteers： a Randomized,Single Dose, Three-period, Six-sequence Crossover Study - 伍三兰;甘珺;饶静;贺思洁;朱雯雯;赵瑛;吕永宁;黄建耿;刘亚妮 (Current medical science, 2017)
Huperzine A is a potent, reversible, and blood-brain barrier permeable acetylcholinesterase inhibitor. The aim of this study was to compare the pharmacokinetics, tolerability, and bioavailability of two formulations with the established reference formulation of huperzine A in a fasting, healthy Chinese male population. This was a randomized, single-dose, 3-period, 6-sequence crossover study. The plasma concentrations of huperzine A were determined by liquid chromatography tandem mass spectrometry. Tolerability was assessed based on subject interview, vital sign monitoring, physical examination, and routine blood and urine tests. The mean（SD） pharmacokinetic parameters of the reference drug were Cmax, 1.550（0.528） ng/m L; t1/2, 12.092（1.898） h; AUC0-72 h, 17.550（3.794） ng·h/m L. Those of the test formulation A and test formulation B were Cmax, 1.412（0.467）, 1.521（0.608） ng/m L; t1/2, 12.073（2.068）, 12.271（1.678） h; AUC0-72 h, 15.286（3.434） ng·h/mL, 15.673（3.586） ng·h/m L. The 90% confidence intervals for the AUC0-72 h and Cmax were between 0.80 and 1.25. No adverse events were reported by the subjects or found with results of clinical laboratory test. The test and reference products met the regulatory criteria for bioequivalence in these fasting, healthy Chinese male volunteers. All three formulations appeared to be well tolerated.